Monitoramento da expressão gênica de Xanthomonas axonopodis pv. citri em diferentes condições ambientais - Defina, Tânia Paula Aquino [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
The bacterium Xanthomonas axonopodis pv. citri is a pathogen causing citric canker that compromises part of the orange production in the State of São Paulo, with negative consequences for the economy of the State and the Country. For the future control of citric canker, several investigators participated in the Xanthomonas Genome Project in order to determine the gene set of this bacterium and to contribute to the identification of the genes involved in its pathogenicity. In this respect, the objective of the current study was to monitor the gene expression of the pathogen when submitted to different environmental conditions such as variation in extracellular pH, and to different antibacterial agents using Differential Display RT-PCR. Using this method we obtained the expression of important genes when the bacteria were submitted to pH 8.0, such as a gene related to an MFS transporter, valine-pyruvate aminotransferase, glucan 1,4--glucosidase and a conserved hypothetical protein. When submitted to the action of inhibitory agents such as ampicillin, Xanthomonas expressed various proteins, i.e., integrase, virulence protein and a phosphoribosylformylglycinamide cycloligase. In a culture containing penicillin, the bacteria expressed the gene of tyrosyl t-RNA synthetase. There is great interest in determining the mechanisms of attack of Xanthomonas axonopodis pv. citri, its interaction with plants and also the strategies it uses to inhibit the defense system of the host, promoting the onset of the disease. In this respect, the present results, added to those obtained in other functional projects, are expected to provide information about the defense mechanism of Xanthomonas and about the plant-bacterium interaction in order to contribute to the control of citric canker

A bactéria Xanthomonas axonopodis pv. citri é um fitopatógeno causador do cancro cítrico que compromete parte da produção de laranjas do Estado de São Paulo, com reflexos negativos para a economia do Estado e do País. Para que haja um controle futuro do cancro cítrico, vários pesquisadores se empenharam no Projeto Genoma-Xanthomonas visando desvendar o conjunto gênico desta bactéria e fornecer subsídios para a identificação dos genes envolvidos com a sua patogenicidade. Neste sentido, o atual trabalho visa o monitoramento da expressão gênica do patógeno quando submetido a diferentes condições ambientais, tais como variações no pH extracelular e antibacterianos utilizando o Differential Display RT - PCR. Deste modo, obtivemos a expressão de genes importantes quando o microrganismo foi submetido ao pH 8.0 tais como: um gene relacionado a um transportador MFS, valina - piruvato aminotransferase, glucano 1,4--glucosidase e uma proteína hipotética conservada. Quando submetida à agentes inibidores como a ampicilina, a Xanthomonas expressou proteínas como a integrase, proteína de virulência e uma fosforibosilformilglicinamida ciclo ligase. Quando em meio de cultura contendo penicilina, a bactéria expressou o gene da tirosil t-RNA sintetase. Há um grande interesse em desvendar os mecanismos de ataque da Xanthomonas axonopodis pv. citri, na sua interação com o vegetal e também suas estratégias para inibir o sistema de defesa do hospedeiro, promovendo o surgimento da doença. Neste sentido, espera-se que estes resultados, adicionados a outros projetos funcionais, possam fornecer informações quanto ao mecanismo de defesa da Xanthomonas, bem como da interação planta-bactéria e conseqüentemente auxiliar no controle do cancro cítrico.
Keywords: Biologia molecular; Cancro citrico; Fitopatologia; Molecular biology